2017
DOI: 10.1111/cbdd.13141
|View full text |Cite
|
Sign up to set email alerts
|

Naphthoquinones: A continuing source for discovery of therapeutic antineoplastic agents

Abstract: Naturally occurring naphthoquinones, usually in forms of botanical extracts, have been implicated with human life since ancient time, far earlier than their isolation and identification in modern era. The long use history of naphthoquinones has witnessed their functional shift from the original purposes as dyes and ornaments toward medicinal benefits. Hitherto, numerous studies have been carried out to elucidate the pharmacological profile of both natural and artificial naphthoquinones. A number of entities ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 91 publications
(117 reference statements)
0
79
0
1
Order By: Relevance
“…[1] They are well represented in numerous natural productsw ith biological activities( e.g.,a ntibiotic, anticancer,antiparasitic) and are generated in many vital metabolic processes. [2] Structurally,t he NQ core, in its oxidized form (NQ ox ), is responsible for its redox properties owing to its ability to accept one or two electrons. In the presence of oxygen, the resulting dihydro-naphthoquinone (NQ red )c an transfer one or two electrons in reactions, regenerating the NQ ox form, and releasing reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] They are well represented in numerous natural productsw ith biological activities( e.g.,a ntibiotic, anticancer,antiparasitic) and are generated in many vital metabolic processes. [2] Structurally,t he NQ core, in its oxidized form (NQ ox ), is responsible for its redox properties owing to its ability to accept one or two electrons. In the presence of oxygen, the resulting dihydro-naphthoquinone (NQ red )c an transfer one or two electrons in reactions, regenerating the NQ ox form, and releasing reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 3-benzoylmenadiones (1)w ere proven to be highlyo xidative compared with the parent menadiones [5] and are proposedt ob et he active components of potent anti-malarial3 -benzylmenadiones. [6] Variation of the substitution pattern at the west or east parts of the electroactive core of NQs [2,7,8] modulates the electrochemical properties and thus both their biological and pharmacokinetic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The ROS plays a central role in cellular survival and function, although cell death was caused by excessive generation of ROS‐induced oxidative stress (Chien et al, ). Some studies show that the highly redox active naphthoquinones undergo one‐electron reduction when the organs with a sufficient blood supply and in an aerobic conditions, and generate free‐radical intermediates, resulting in the accumulation of ROS (Qiu et al, ; Wellington, ). Our study indicated that NTDMNQ induced apoptosis through increasing intracellular ROS levels (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%
“…However, this multitargeting property could be exploited to design multitarget drugs, thus providing better responses and lower sensitivity to drug resistance than monotherapies . Moreover, these possible adverse effects could be reduced by structural modification, co‐administration or the use of a suitable delivery system …”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, these possible adverse effects could be reduced by structural modification, co-administration or the use of a suitable delivery system. 14 In a previous study 4 we evaluated the phytotoxic potential and transport phenomena of acyl and alkyl derivatives with different chain lengths on the juglone and lawsone scaffolds in an effort to enhance the activity of the bioactive parent quinones. The results showed a significant correlation between the different bioassays performed to identify and select the lead compounds, and a marked influence was observed on the activity depending on the modified position of the naphthoquinone backbone.…”
Section: Introductionmentioning
confidence: 99%